Language and Identity in Multilingual Mediterranean Settings : Challenges for Historical Sociolinguistics - Molinelli, Piera (Trends in linguistics. Studies and monographs, 2017)
This book explores the linguistic expression of identity, intended as the social positioning of self and others, by focusing mostly on a scenario of prolonged language contact, namely the ancient Mediterranean area. The volume includes studies on language contact and on identity strategies developed at different levels of analysis, from phonetics to pragmatics, in, among others, Latin, Greek, Coptic, Syriac, (Cypriot) Arabic, Medieval Sardinian.